2011
DOI: 10.1007/s11060-011-0532-6
|View full text |Cite
|
Sign up to set email alerts
|

MGMT promoter methylation and immunoexpression in aggressive pituitary adenomas and carcinomas

Abstract: MGMT promoter hypermethylation of aggressive pituitary adenomas and pituitary carcinomas and low protein expression are implicated in improved response to treatment with temozolomide (TMZ). The aim of the present study was to investigate MGMT promoter methylation and immunoexpression in an aggressive subset of pituitary adenomas and carcinomas. Our material consisted of 12 silent subtype 3 (SS3) adenomas, 10 primary carcinomas, and 4 disseminated metastases. Two different tissue samples of 7 of the 12 SS3 aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 52 publications
0
32
1
3
Order By: Relevance
“…TMZ has been suggested to be effective also in pituitary adenomas harboring a methylated MGMT gene promoter, as is the case in gliomas (20,21). Salehi et al (22) reported that there was no relationship between MGMT promoter methylation status and MGMT immunoexpression. Although the changes in MGMT expression in recurring pituitary tumors could affect adenoma progression and TMZ efficacy, MGMT is not the sole molecular factor determining sensitivity to TMZ.…”
Section: Discussionmentioning
confidence: 99%
“…TMZ has been suggested to be effective also in pituitary adenomas harboring a methylated MGMT gene promoter, as is the case in gliomas (20,21). Salehi et al (22) reported that there was no relationship between MGMT promoter methylation status and MGMT immunoexpression. Although the changes in MGMT expression in recurring pituitary tumors could affect adenoma progression and TMZ efficacy, MGMT is not the sole molecular factor determining sensitivity to TMZ.…”
Section: Discussionmentioning
confidence: 99%
“…The value of MGMT status as a predictor of TMZ response in aggressive pituitary tumours is less clear. Promotor methylation of the gene occurs less frequently in pituitary tumours, and MGMT measured by PCR-based methods has not been associated with response to TMZ (11,102,107,111,130). The reasons are not understood and may involve mechanisms regulating MGMT expression independent of promotor methylation.…”
Section: Reasoningmentioning
confidence: 99%
“…A significant inverse correlation was found between IHC MGMT expression and response to TMZ; however, the absence of MGMT expression was not always predictive of tumor response [113,115]. On the contrary, studies examining MGMT promoter methylation in pituitary tumors confirmed its poor prognostic value since methylated MGMT promoter was found only in 60% of TMZ-sensitive tumors and 50% of TMZ-resistant tumors [96,119]. It appears that MGMT IHC but not MGMT promoter methylation status can be used to predict response to treatment in pituitary tumors.…”
Section: Treatmentmentioning
confidence: 99%